Prevalence of Dental Caries and the Effectiveness of Demonstration on Dental among Primary School Students in Selected Schools of Rural Community, Assam (International Journal of Nursing Education, 2020)
Introduction: Oral health promotion through schools is recommended by WHO for improving knowledge,attitude and behaviour related to oral health and for prevention of dental diseases among school children.In India, 70 -72% of population live in the rural areas of which more than 40% are children. These childrentend to be more vulnerable to oral health problems.Aim and Objective: To assess prevalence of dental caries and the effectiveness of demonstration on dentalhygiene among primary school students.Material and Method: The study was a cross?sectional study conducted at selected schools of Rani ruralcommunity of Kamrup District, Assam. 118 primary school students of class IV and V were selected usingconsecutive sampling technique. The subjects were assessed for the presence of dental caries using dmftscoring and observed for their practice of brushing with Fones method of brushing. Later demonstrationfor the Fones method was given to the participants and post test was done to evaluate the effectivenessof demonstration. The collected data was analyzed using SPSS version 20 software. Results: The studyshowed that more than half i.e., 92 (78%) of the students have dental caries. It was found that in pre-test,79 (61%) of the participants have good practice of dental hygiene which was increase to 93 (78.8%) in posttest. Again, in pre-test 46 (39%) of the participants have poor practice of dental hygiene, which was reducedto 25 (21.2%) in post test. The mean post test practice score (7.03) is higher than the mean pre test practicescore (4.70) of dental hygiene. The median post test practice score (7) is also higher than the median posttest practice score (5) of dental hygiene and the post test SD (0.67) seems to be less disperse than the pre testSD (0.73) of dental hygiene. It also shows that the “t” value (-28.482) and p -value 0.00 is highly significantat 0.05 level of significance. So it is evident that the demonstration on Fones method of brushing is effectivein increasing the dental hygiene practice among the students.Conclusion: Regulating good practice of dental hygiene is important during the early school period. Ashealth personnel, community nurse can take active role in imparting information on dental hygiene practiceamong students by conducting school health programme and demonstrating on brushing technique. And alsorecommending inclusion of dental hygiene in the curriculum of the school.
Keywords: Practice of dental hygiene, Fones method of brushing.